Persepsi Guru dan Orang Tua: Implementasi Experiential Learning pada Pendidikan Anak Usia Dini - Muhammad Abdul Latif; Sangkot Sirait (PSGA LP2M IAIN Pontianak, 2022)
Learning problems become a study that is always reviewed to facilitate students in the learning process. Conventional learning that is constantly being applied in educational institutions in Indonesia, especially Early Childhood Education (PAUD) by means of teachers giving lectures then students listen to it and the teacher gives worksheets to children without regard to children's interests or interests. This article is structured to provide a study of experiential learning in PAUD which is seen from the perspective of the understanding of teachers and parents. The research method used is qualitative with a case study approach. The subjects of this study consisted of principals, teachers, volunteers and parents or guardians of TA SALAM Yogyakarta students. Data collection techniques using semi-structured interviews with data analysis coding. The results of this study indicate that teachers' perceptions about experiential learning in PAUD are in accordance with the theory put forward by David A. Kolb and Experiential learning is very suitable to be applied in PAUD.